Književni pouk v osnovni šoli med tradicijo in sodobnostjo - Medved-Udovič, Vida (Jezik in slovstvo, 2019)
The article addresses the topic of teaching literature in primary school in the light of certain concerns expressed at the conference (Ljubljana, 2017) on the placement and treatment of literary texts from literary folklore, antiquity and the Bible in the Slovenian Curriculum in Primary School (Učni načrt za slovenščino, 2011) and in the readers currently used in primary school. Based on a review of the curriculum and selected readers, it was found that the presence and treatment of such texts is evident in both the curriculum and the readers. When treating such texts, it is especially important that the didactic instruments used take into account the reception capacities of students of different ages and their active contact with the proposed texts. The latter is encouraged and developed by the communicative approach to teaching literature.
Keywords: berila; didaktika; književnost; osnovnošolski pouk; pouk književnosti; učni načrti za slovenščino; žanri slovstvene folklore